Message-ferrying delay-tolerant routing in linear wireless sensor networks. (6th May 2022) - Jawhar, Imad; Zhang, Sheng; Wu, Jie; Mohamed, Nader
Due to linearity of a monitored structure, wireless sensor network (WSN) topology exhibits a linear form and the resulting network is named a linear sensor network (LSN). In order to communicate data from sensor nodes (SNs) to the sink, a multi-hop approach can be used. However, this would result in significant transmission energy loss, as the SNs would be involved in the transmission of their data as well as the data from other sensor nodes. In this paper, we introduce a ferry-based LSN (FLSN) model, where a ferry node such as a robot or other types of moving vehicles goes along the LSN, collects the data from the SNs and delivers it to the sink at the end of the network. Overall, this approach saves SN energy, increases network lifetime, and reduces transmission interference. Four ferry movement algorithms are presented, simulated and analysed under various network conditions.